2023
DOI: 10.1007/s12311-023-01570-0
|View full text |Cite
|
Sign up to set email alerts
|

P300 Wave Alterations and Cognitive Impairment in Cerebellum Lesions

Abstract: Patients with cognitive deficits have a prolonged latency and reduced amplitude of the P300 wave. However, no study has correlated P300 wave alterations with the cognitive performance of patients with cerebellar lesions. We aimed to determine if the cognitive status of these patients was associated with P300 wave alterations. We recruited 30 patients with cerebellar lesions from the wards of the N.R.S. Medical College, Kolkata, in West Bengal (India). The Kolkata Cognitive Screening Battery tasks and the Front… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Studies have indicated that the frontoparietal lobe plays a crucial role in regulating attentional resources ( Zhang et al, 2022 ), and there is functional connectivity between the cerebellum and the frontoparietal lobe ( Ruan et al, 2023 ). Reductions in P300 amplitude have been observed in patients with cerebellar injury ( Rodriguez-Labrada et al, 2019 ; Nanda et al, 2023 ), suggesting the cerebellum’s involvement in attentional resource allocation. Another study linked the early reduction in P3b wave amplitude following cerebellar infarction to dysfunction in cerebellar projections to the prefrontal and posterior parietal cortex ( Mannarelli et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that the frontoparietal lobe plays a crucial role in regulating attentional resources ( Zhang et al, 2022 ), and there is functional connectivity between the cerebellum and the frontoparietal lobe ( Ruan et al, 2023 ). Reductions in P300 amplitude have been observed in patients with cerebellar injury ( Rodriguez-Labrada et al, 2019 ; Nanda et al, 2023 ), suggesting the cerebellum’s involvement in attentional resource allocation. Another study linked the early reduction in P3b wave amplitude following cerebellar infarction to dysfunction in cerebellar projections to the prefrontal and posterior parietal cortex ( Mannarelli et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the P3b component reflects attention to task-relevant information and is linked to memory and descending adrenergic parietal activity ( Polich, 2007 ; Masson and Bidet-Caulet, 2019 ; Riby et al, 2023 ). Previous studies, including those examining cerebellar cognitive function ( Rodriguez-Labrada et al, 2019 ; Nanda et al, 2023 ), have demonstrated the vital role of the P300 component in uncovering the involvement of the cerebellum in cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%